PERAN DAN KOMPETENSI GURU DALAM E-LEARNING - Nugraheni, Endang (Jurnal Pendidikan, 2009)
<div id="summary" class="item article-summary" style="box-sizing: border-box; padding: 20px 0px; color: #333333; font-family: ’Source Sans Pro’, ’Helvetica Neue’, Helvetica, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f5fcf2; text-decoration-style: initial; text-decoration-color: initial;"> E-learning has been growing rapidly despite its pros and cons. Good e-learning is based on principles and pedagogy similar to other type of leaming. Align with the shift of educafional paradigm from teacher-centered to student-centered, sooner or later teachers should adapt themselves to the new roles. This article discusses teachers’ roles and competencies related to e-learning.